229k views
0 votes
1/3 (2x - 1) = z for x

1 Answer

2 votes

We need to solve the equation shown below for x:


(1)/(3)(2x-1)=z

Using distributive propery, a(b - c) = ab - ac , we can simplify the left hand side:


\begin{gathered} (1)/(3)(2x)-(1)/(3)(1)=z \\ (2)/(3)x-(1)/(3)=z \end{gathered}

We isolate the term with x and then divide the other side by 2/3 to get x = something...


\begin{gathered} (2)/(3)x-(1)/(3)=z \\ (2)/(3)x=z+(1)/(3) \\ x=(z+(1)/(3))/((2)/(3)) \end{gathered}

To simplify it (reduce), we can divide both terms by (2/3) and simplify. Shown below:


\begin{gathered} x=(z)/((2)/(3))+((1)/(3))/((2)/(3)) \\ x=z*(3)/(2)+(1)/(3)*(3)/(2) \\ x=(3z)/(2)+(1)/(2) \\ x=(3z+1)/(2) \end{gathered}

The final answer:


x=(3z+1)/(2)

User Hanumant
by
5.1k points